Pembuatan Instrumen Penilaian dengan Aplikasi Genially Sebagai Upaya Peningkatan Mutu Guru MA Miftahul Ulum Bojonegoro - Fauziah, Zumrotul; Nihayah, Hamidatun; Minarti, Sri (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: In this digital era, teachers are required to be able to adapt and integrate technology in learning. Most of the Madrasah Aliyah Miftahul Ulum Bulu Balen teachers do not have adequate knowledge and skills in utilizing information technology in learning so they still use conventional teaching methods. Providing training in creating gamification-based assessment instruments with a friendly application. Method: The partner in this service is Madrasah Aliyah Miftahul Ulum Bulu Balen Bojonegoro. There were 14 participants from the teacher council. The method used is training through five stages, namely FDG, material determination, planning, implementation and evaluation. Results: Teachers can create gamification-based assessment instruments with the Genially application. They assess students' knowledge in a more interesting and fun way because the questions are presented in the form of games and quizzes for students to complete. With the variety of quizzes and gamification in the Genially application, teachers can use different types of games for each material. Conclusion: The level of participants' understanding (the teacher's ability and skills in using technological information) was 85% greater than participants who did not or did not understand.